Five new rotundabaloghiid mites (Acari: Uropodina) from South-East Asia - Kontschán, Jenő; Kiss, Balázs (Zootaxa, 2015)
Five new species of the family Rotundabaloghiidae are described from Indonesia and Malaysia. Angulobaloghia pedunculata sp. nov. differs from the other Angulobaloghia Hirschmann, 1979 species in the shape of the genital shield of the female. Rotundabaloghia (Rotundabaloghia) wangi sp. nov. has one pair of short and pilose setae (V8) on the ventral idiosoma, which is unique in the subgenus Rotundabaloghia (Rotundabaloghia) Hirschmann, 1975. Rotundabaloghia (Circobaloghia) javaensis sp. nov. has a small triangular anterior process on genital shield of female, which has not been detected previously in South-East Asian members of this subgenus. The long and thick ventral seta (V4) in Depressorotunda (Depressorotunda) robusta sp. nov. is a character state so far unknown in the subgenus Depressorotunda (Depressorotunda) Kontschán, 2010. Depressorotunda (Depressorotunda) hirca sp. nov. has two apically serrate anterior branches on the margin of the female genital shield.